Mutation accumulation in H. sapiens F508del CFTR countermands dN/dS type genomic analysis. - Jeong S Hong; Janice M Tindall; Samuel R Tindall; Eric J Sorscher (PLoS ONE)
Understanding the mechanisms that underlie de novo mutations (DNMs) can be essential for interpreting human evolution, including aspects such as rapidly diverging genes, conservation of non-coding regulatory elements, and somatic DNA adaptation, among others. DNM accumulation in Homo sapiens is often limited to evaluation of human trios or quads across a single generation. Moreover, human SNPs in exons, pseudogenes, or other non-coding elements can be ancient and difficult to date, including polymorphisms attributable to founder effects and identity by descent. In this report, we describe multigenerational evolution of a human coding locus devoid of natural selection, and delineate patterns and principles by which DNMs have accumulated over the past few thousand years. We apply a data set comprising cystic fibrosis transmembrane conductance regulator (CFTR) alleles from 2,393 individuals homozygous for the F508del defect. Additional polymorphism on the F508del background diversified subsequent to a single mutational event during recent human history. Because F508del CFTR is without function, SNPs observed on this haplotype are effectively attributable to factors that govern accumulating de novo mutations. We show profound enhancement of transition, synonymous, and positionally repetitive polymorphisms, indicating appearance of DNMs in a manner evolutionarily designed to protect protein coding DNA against mutational attrition while promoting diversity.